6a-4whena=6

Simple and best practice solution for 6a-4whena=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-4whena=6 equation:


Simplifying
6a + -4whena = 6

Solving
6a + -4aehnw = 6

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Reorder the terms:
-6 + 6a + -4aehnw = 6 + -6

Combine like terms: 6 + -6 = 0
-6 + 6a + -4aehnw = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-3 + 3a + -2aehnw) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-3 + 3a + -2aehnw)' equal to zero and attempt to solve: Simplifying -3 + 3a + -2aehnw = 0 Solving -3 + 3a + -2aehnw = 0 Move all terms containing a to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3a + 3 + -2aehnw = 0 + 3 Reorder the terms: -3 + 3 + 3a + -2aehnw = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 3a + -2aehnw = 0 + 3 3a + -2aehnw = 0 + 3 Combine like terms: 0 + 3 = 3 3a + -2aehnw = 3 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 3k^2-k-18=6 | | 66+(-81)= | | 75x-2=9x+2 | | 5n^2+41n+5=-3 | | (x+y)+77= | | 5x+10x-2=3(5x+9) | | 18-9(9-8)= | | 3X+17=6X-34 | | 12+7x-21=-8(3-x)+3x | | 5cos^2-3cosx=2 | | 2.5x=37.5 | | 6(8x+5)=48x-1 | | 2.7x=37.5 | | 4x+31x-5=7(5x+9) | | 11(3x-8)=88x | | 4x+x+6=11x-6x | | 5X+12=7X-26 | | 2(4x+3)=11x+3-3x+3 | | 7x+19x-5=7(4x+7) | | (6x+2)(3x-8)=x(4x+17) | | 3X-7=2X-14 | | -4x-(-10.5)=2.7 | | 3x+12-4=0 | | 2x-13=5x-28 | | t=7+4h | | y=-4x^2-2116 | | 3x+9=x+14 | | 10cx+7b=4cx+d | | 7x-7=2x+33 | | 8x-9=3x+41 | | 0.08*x=13.6 | | 16X-(8X-2)=66 |

Equations solver categories